2022
DOI: 10.3390/vaccines10091415
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against SARS-CoV-2 Alpha, Beta, and Gamma Variants in Pregnant Women and Their Neonates under Antenatal Vaccination with Moderna (mRNA-1273) Vaccine

Abstract: The aim of the study was to examine the impact of COVID-19 vaccination on the anti-SARS-CoV-2 spike receptor binding domain IgG antibody (SRBD IgG) binding ratio (SBR) from Alpha, Beta, and Gamma variants of SARS-CoV-2 in pregnant women and neonates. The impact of antenatal influenza (flu) and pertussis (Tdap) vaccines was also studied. We enrolled pregnant women vaccinated with the Moderna (mRNA-1273) vaccine during pregnancy and collected maternal plasma (MP) and neonatal cord blood (CB) during delivery to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 61 publications
1
6
0
3
Order By: Relevance
“…Our previous research reported that 2-dose vaccinations produced greater Nab inhibition for various strains of SARS-CoV-2 including wildtype, alpha, beta, gamma, and delta type, than 1-dose vaccinations according to values observed in maternal blood and corresponding neonatal cord blood ( Shen et al., 2022 ; Chen et al., 2022a ). Other research reported in the literature has indicated that booster COVID-19 vaccination can produce a more potent Nab response against the Omicron SARS-CoV-2 variants including several novel subvariants ( Lin et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research reported that 2-dose vaccinations produced greater Nab inhibition for various strains of SARS-CoV-2 including wildtype, alpha, beta, gamma, and delta type, than 1-dose vaccinations according to values observed in maternal blood and corresponding neonatal cord blood ( Shen et al., 2022 ; Chen et al., 2022a ). Other research reported in the literature has indicated that booster COVID-19 vaccination can produce a more potent Nab response against the Omicron SARS-CoV-2 variants including several novel subvariants ( Lin et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination against COVID-19 for pregnant women allow mothers to produce and transfer protective antibodies to their fetus ( Shen et al., 2022 ). Specifically, the transplacental transmission of SARS-CoV-2 neutralizing antibodies (Nabs) has shown potential in protecting fetuses and neonates ( Shen et al., 2022 ; Chen et al., 2022a ), and this protection can also be observed for newly-evolved SARS-CoV-2 variants including Omicron variants ( Chen et al., 2022b ; Munoz et al., 2023 ). According to current research, COVID-19 vaccination in pregnant women does not increase the risk of any adverse pregnancy, maternal, or neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…De igual forma Chen et al (23) , determinan que dos dosis de la vacuna mejoraban la unión (SBR) del anticuerpo IgG, contra las variantes alfa, beta y gamma del SARS-CoV-2 que aquellas mujeres quienes solo se colocaron una única dosis.…”
Section: Discussionunclassified
“…Por último, es válido destacar, Chen et al (23) a su vez mencionan que la relación de unión (SBR) aportada por la vacuna Moderna (ARNm-1273) del anticuerpo IgG al receptor de picos antiSARS-CoV-2, fue mucho mayor para las variantes alfa que las beta y gamma. Aunque, Gray et al (24) , concuerdan y mejoran los aportes científicos, mencionando que vacunas de ARNm generan una inmunidad humoral más robusta en gestantes, lactantes y no embarazadas.…”
Section: Discussionunclassified
See 1 more Smart Citation